(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Society-based research subjects are the study of sociology which is an importantbranch of science in the field of social science. It is a branch of studying society, social values, social groups, social classes and economical, political, social, religious, lawfulinstitutions, population, usage, custom, value, norm, beliefs and relations and changesbetween them. In this context, sociology gains sociological thinking skill with its own peculiar methodology, and therefore it helps complex social events to be understoodbetter. Giving the faculty of looking at sociological events with the eye of sociology and sociological thinking to individuals in educational process in early ages will enable thefaculty of „understanding‟ of society and social events to be more established andsystematic. It is an urgent need of using teaching methods and techniques leading to critical sight which is the basement of sociology, instead of passive student profileresulting from use of traditional teaching methods and techniques in teachingsociology. It is known well that as a need of modern education understanding, thisrequirement exists physically in teaching programs but educators are in difficulty of application of new techniques. The main goal of this study is to emphasize the application of modern teaching techniques in teaching sociology actively. For this reason, application of producing ideatechniqueisgoing to be realized in teaching of sociology. Key words: Teaching of sociology, modern teaching techniques, producing idea.